RODZINA VON STENTSCH – WŁAŚCICIELE PRZYTOKU W XVI-XIX WIEKU - Małgorzata Konopnicka (In Gremium. Studies in History, Culture and Politics, 2018)
At the beginning of the early modern period the village of Przytok, located in Zielona Góra weichbild, was owned by von Burgsdorff family, then von Tschammer family, and in 1591 it was sold to Joachim von Stentsch. The history of this village was connected with the history of the family until the beginning of the 19th century. The most important members of the family included: the aforementioned first owner of Przytok, Joachim, and his successor, Johann Georg, who established a folwark village – Jany and founded a church in Przytok. He also held public offices in the court system of the Duchy of Głogów. An important person in the history of the family and the discussed village was also Maximilian Adolph von Stentsch, who was Landrat of Zielona Góra County for many years (till 1783) and he apparently was really successful as he was considered to be one of “three favourite Silesian Landrats” of Frederick II. Moreover, he was also the sponsor of a new evangelical church, which was able to accommodate up to 600 people.